Pengembangan Menu Gizi Seimbang dan Status Gizi Santri Remaja Di Jakarta Selatan: Pengembangan Menu Gizi Seimbang dan Status Gizi Santri Remaja di Jakarta Selatan - Camila, Faiza; Sofianita, Nur Intania; Fatmawati, Iin; Ilmi, Ibnu Malkan Bakhrul (Amerta Nutrition, 2023)
Background: Nutritional intake problems are common among santries due to a lack of varied balanced nutritional menus, which impacts nutritional status. As a result, menu modifications are required to improve santries nutritional status. Objectives: Creating a balanced nutritional menu and understanding the relationship between daily intake and nutritional status of the santries. Methods: Using mixed methods quantitatively and experimentally. The research subjects used a quota sampling of 25 santries as well as untrained panelists and 15 semi-trained panelists, namely nutrition students who were experienced in organoleptic testing. Intake data from 2x24 hour food recall and nutritional status data from anthropometric measurements. The development of a balanced nutritional menu is adjusted to the results of monitoring and filling out questionnaires regarding preferences for food ingredients. Data analysis uses the Spearman test to determine the relationship between variables. Results: There is a relationship between energy intake (p-value = 0.050), protein intake (p-value = 0.005), and fat intake (p-value = 0.018) and student nutritional status; however, there is no relationship between carbohydrate intake (p-value = 0.188). The santries's fiber intake is still below the Nutritional Adequacy Rate, and the rainbow tofu hotpot is the result of developing a balanced nutritional menu that the santries enjoy the most. Conclusions: The nutritional status of santries's related to their energy, protein, and fat intake. There is no link between carbohydrate intake and student nutritional status. "Rainbow Tofu Hotpot” is a nutritionally balanced menu that santries prefer in terms of color, taste, aroma, and texture.